Use of Milk-Protein Concentrates in the Production of Fermented Milk Products - Gutоv , Nikolay; Maseeva, Irina (KnE Life Sciences, 2021)
There are an increasing number of products containing milk-protein concentrates. Their use helps to reduce the duration of the fermentation process; increases the concentration of viable cells of lactic acid microorganisms; creates the desired consistency of finished products with required structural and mechanical properties; improves the taste; expands the range of fermented milk products; increases the content of essential amino acids and regulates the amino acid composition; increases the product yield; and improves the manufacturability, including the turnover of the main technological equipment and production areas. This article presents the results of the use of milk-protein concentrates in the production of sour milk, cream and cottage cheese. The acidity of test samples, their biological value, and the total amount of lactic acid microorganisms were determined. The research results show that the use of milk-protein concentrates in the production of dairy products contributes to the intensification of the technological processes and improves the quality of the finished products. Keywords: casein, milk protein, milk protein concentrate, whey proteins, lactic acid microorganisms, biological value